Effect of vinylene carbonate electrolyte additive and battery cycling protocol on the electrochemical and cyclability performance of silicon thin-film anodes. (February 2022) - Salah, Mohammed; Pathirana, Thushan; de Eulate, Eva Alvarez; Hall, Colin; Kerr, Robert; Fabretto, Manrico
Highlights: A multi-faceted approach is essential for producing Si anodes with enhanced capacity retention. Vinylene carbonates addition to a standard electrolyte positively impacts the performance of Si film anodes. Optimization of upper and lower cut-off voltages is essential for the performance of Si film anodes. Depth of discharge is a good pathway to increase the cycle life of Si anodes. Abstract: The use of silicon as a replacement for graphite, the commonly utilised anode material, would help increase the energy density of lithium-ion batteries, as it has a significant specific capacity of 4200 mAh/g compared to only 372 mAh/g for graphite. However, the high electronic resistivity and low mechanical stability of silicon have hindered its commercial uptake. In this contribution, we have employed a multifaceted approach in order to enhance the capacity retention of pure silicon anodes. The effect of adding 5 vol. % vinylene carbonates to a standard electrolyte has been examined with respect to the performance of physical vapour deposited pure Si thin films. Changes in battery cycling parameters (i.e., lower and upper cut-off voltages and depth of discharge were examined using charge/discharge cycling, cyclic voltammetry, and electrochemical impedance spectroscopy, indicating that cycling stability and electrochemical performance of the anodes were heavily influenced by these changes. The effect of each procedure (i.e., electrolyte additive and battery cycling protocol) on the initial discharge capacity, initial coulombic efficiency, initial irreversible capacity, capacity retention, and the lithium-ion diffusion coefficient into the silicon anode was examined. The Si film with optimised: deposition conditions, electrolyte additives, and battery testing protocol had a discharge capacity of 1740 mAh/g and capacity retention of 92 % at a charge/discharge rate of C/2 after 1000 cycles.